2009
DOI: 10.1103/physrevb.80.153203
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of defect-induced intrinsic ferromagnetism in III-V nitrides: The case of BN

Abstract: We report the synthesis and magnetic properties characterizations of defective BN obtained from a modified solid-state reaction. X-ray diffraction analysis indicated the presence of two crystalline phases of BN in products. No magnetic impurities, such as Fe, Co, Mn, and Ni were detected by chemical analysis. Transmission electron microscopy observation and photoluminescence spectrum measurement showed the existence of large-scale defects in BN lattices. Magnetic measurement undoubtedly demonstrated the typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Dev et al (161) suggested that defects such as cation vacancies could induce intrinsic long-range magnetic order in BN. Intrinsic ferromagnetism at room temperature has been observed in graphene-like BN and is expected to arise from free spins that become available due to conversion of sp 3 to sp 3 -sp 2 hybridization or from the unpaired spin electron from the defects (162). Figure 11c shows room-temperature ferromagnetism of few-layer BN.…”
Section: Magnetic Propertiesmentioning
confidence: 97%
“…Dev et al (161) suggested that defects such as cation vacancies could induce intrinsic long-range magnetic order in BN. Intrinsic ferromagnetism at room temperature has been observed in graphene-like BN and is expected to arise from free spins that become available due to conversion of sp 3 to sp 3 -sp 2 hybridization or from the unpaired spin electron from the defects (162). Figure 11c shows room-temperature ferromagnetism of few-layer BN.…”
Section: Magnetic Propertiesmentioning
confidence: 97%
“…There has recently been tremendous interest in understanding the origin of room temperature unconventional ferromagnetism observed in a variety of materials that are nonmagnetic in their bulk forms [1][2][3]. Over the last decade, many groups have focused on doped, transition or rare earth, compound semiconductors such as Co:TiO 2 [4], Co:ZnO [5], Li:SnO 2 [6], and Cr:In 2 O 3 [7] due to their prospective applications in spintronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it is well established that the nitrogen and/or aluminium vacancies prefer spin polarisation and can give rise to magnetic order beyond certain concentration [16][17][18]. The native defects have been shown to even enhance the magnetisation in TM doped AlN matrix [5,8,19].…”
Section: Introductionmentioning
confidence: 93%